IMPACT OF PERSONAL MOBILITY DEVICES ON THE RISK OF MAXILLOFACIAL INJURIES ACROSS DIFFERENT AGE GROUPS - Boymuradov Shukhrat Abdujalilovich; Khatamov Ulugbek Altibayevich (Journals Park Publishing, 2024)
Currently, there is a high demand for personal mobility devices, particularly "electric motor scooters." Today, this type of transport is widespread among modern countries, including Central Asian countries, and our country, Uzbekistan, is no exception. It has gained a place among other nations in making personal mobility devices available for public use.
Keywords: personal mobility devices (PMDs), negligence, protective gear, software, lethality, maxillofacial injuries.